Public Administration in Italy in Political and Historical Context
XXXIII, 273 p. 19 illus.
Keywords: This book is one of three volumes that provide a systematic overview of public administration, public management and public governance in Italy. This first volume examines the broad societal, institutional and political context of public administration in the country. It provides an overview of the trajectory of administrative reforms since the establishment of Italy as a unitary state in 1861 to the present, and analyses key components of the functioning of the administrative system, including strategic planning, financial management, expenditure management, spending reviews, transparency and performance management. It also considers trajectories of reform of public services in key policy sectors, such as healthcare, social care, and higher education. Chapters are written by some of the leading experts of public administration in Italy, including economists, historians, lawyers, political scientists and public management scholars, some of whom have also served in positions of direct administrative responsibility in the Italian public sector. The book will appeal to students and scholars of public administration, public management and public governance, as well as practitioners with an interest in Italy. Edoardo Ongaro is Professor of Public Management at The Open University, UK. Carla Barbati was Professor of Administrative Law at IULM, and Councillor of State of Italy. Fabrizio Di Mascio is Professor of Political Science at the University of Turin, Italy. Francesco Longo is Associate Professor of Public and Health Care Management at the Department of Social and Political Sciences, Bocconi University, and Senior Professor at the SDA Bocconi School of Management, Italy. Alessandro Natalini is Professor of Political Science at LUMSA, Italy.